Two new species of Psyllocarpus (Spermacoceae, Rubiaceae) from the state of Minas Gerais, southeastern Brazil - Sobrado, Sandra V.; do Carmo, João A.M.; Simões, André O.; Salas, Roberto M. (European Journal of Taxonomy, 2022)
Two new species of Psyllocarpus sect. Psyllocarpus, P. itakangapyra Sobrado, J.A.M.Carmo & R.M.Salas sp. nov. and P. vianae Sobrado, J.A.M.Carmo & R.M.Salas sp. nov., from the “campo rupestre” of the state of Minas Gerais, southeastern Brazil, are here described and illustrated. We provide comments on their distribution, habitat, and preliminary conservation status, and discuss their taxonomy. In addition, we analyse floral, fruit, and seed micromorphology, as well as pollen grains of the new species. We also provide an updated identification key to the species of P. sect. Psyllocarpus.